Uji Senyawa Bioaktif Dan Toksisitas Limbah Cangkang Kerang Hijau (Pera Viridis) - Suhaera Suhaera; Aprilya Sri Rachmayanti; Shinta Sari Dewi; St. Mursyidah; Dachriyanus Dachriyanus (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Green mussels are organisms belonging to the class pelecypoda, this class has two bilaterally symmetric valve shells, these green mussels are referred to as bivalves, and are included in the soft-bodied marine biota (Mollusca). This study aims to determine the bioactive compounds and toxicity contained in the shells of green mussels (Perna viridis) which are processed seafood typical of the Riau Islands. Secondary metabolite screening tests include alkaloids, flavonoids, tannins, saponins, steroids and terpenoids as for toxicity tests using the BSLT (Brine Shrimp Lethality Test) method with shrimp larvae (Artemia salina Leach) test animals. The results of secondary metabolite screening on the test for alkaloids, flavonoids, tannins, steroids and terpenoids were declared negative while the saponin test was positive with the formation of stable foam. The results of the BSLT toxicity test (Brine Shrimp Lethality Test) with concentrations of 10 ppm, 100 ppm, and 1000 ppm obtained LC50 <1000 g/ml, which is 1127.28 ppm in the non-toxic category. In the sense that it is safe to be used as processed food.